Comportamento ingestivo e alterações cardiovasculares em ratos com hipertensão renovascular 2 rins-1 clipe tratados com inibidor da enzima conversora de angiotensina - Cunha, Francisco Mateus Pereira (2023)
Hypertension is a worldwide public health problem that represents a high risk for other cardiovascular and renal diseases, including about 667,184 deaths due to hypertension were recorded in Brazil between 2008 and 2017. Considering this, it is important that further studies seek to better understand the pathophysiology and new therapeutic methodologies for the treatment of this disease. The 2 kidneys 1 clip (2R1C) renovascular hypertension is an experimental model characterized by increased activity of the renin angiotensin system (RAS), sympathetic activity and daily water and hypertonic NaCl intake, in addition to cardiac remodeling/hypertrophy. However, the role of angiotensinergic activity in changes in water and NaCl intake behavior and cardiac hypertrophy in this model is not yet well established. Thus, it is possible to speculate that angiotensin-converting enzyme blockade may be able to modify the ingestive behavior and cardiovascular changes in rats with renovascular hypertension 2R1C. The aim of the present study was to investigate whether angiotensin-converting enzyme blockade modifies the ingestive behavior and cardiovascular changes of 2R1C hypertensive rats. Wistar rats weighing between 150 and 180 grams were used for induction of 2R1C renovascular hypertension. Treatment with enalapril (3 mg/kg/day; 14 days) was started at the 15th day after the 2K1C surgery, i.e., during the hypertension development phase. Seven days after the beginning of the treatment with enalapril, daily records of water and 0.23 M NaCl intake were performed and, at the end of the experiment, the heart was collected to determine cardiac weight and volume. Partial stenosis of the renal artery, with an intact contralateral kidney, induced an increase in systolic blood pressure and, consequently, mean arterial pressure, with no change in heart rate. Enalapril-treated 2K1C rats ingested a greater volume of NaCl compared to sham, but there was reduced water intake in this group. Both 2K1C hypertensive groups had increased heart weight, but no change in heart volume, compared to sham animals. Thus, the results of the present study show that angiotensin-converting enzyme blockade with enalapril at a dose of 3 mg/kg was not able to reduce cardiovascular variables in 2K1C hypertensive rats, but induced a significant increase in 0.23 M NaCl intake and reduced water intake.